Pelatihan Dan Edukasi Kerajinan Tangan Manik-Manik Untuk Kemandirian Ekonomi Anak Panti Asuhan Ummu Aiman - Jasri, Jasri; Egidia syafitri; Syek Abdullah; Waode Nurhaliza; Rifka Alfiana; Sulfiani, Sulfiani; Iksan, Iksan; Nurul Insyani; Eva Nunung Husna; Titin Nurfadilla; Nadiatul Imani; Asma Amelia; Iftita Annur; Maulana Malik Ibrahim; Zulfitrah Amal; Anwar Kadafi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This Community Service (PKM) activity was carried out at the Ummu Aiman Orphanage, Makassar City. This activity aims to build entrepreneurial character in the orphanage children through training in craft skills using recycled materials. Through an educational and applicative approach, participants were trained to create products such as pencil cases from plastic bottles, decorated with hemp rope, beads, and ribbons. In addition to technical skills, the training also emphasized values such as hard work, honesty, responsibility, and an introduction to basic digital marketing platforms. The results showed an increase in practical abilities, self-confidence, and an understanding of the economic value of the products. This program is expected to be the initial foundation for the economic independence of orphanage children in the future.